Pengembangan Buku Ajar Keterampilan Menulis Bahasa Arab Berbasis Kearifan Lokal Sebagai Penunjang Kreativitas Mahasiswa - Zaim Elmubarok; Darul Qutni; Muchlisin Nawawi (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2019)
Basic Arabic writing skills are included in the competency-based curriculum and conservation of the Arabic Education Study Program. Learning basic Arabic writing skills is provided through the taroqib wa takhawiljumal course. Learning basic Arabic writing skills, based on local wisdom, introducing our nation's culture and increasing students' creativity in writing Arabic. The research subjects were students who took taroqib wa takhawiljumal totaling 30 people, data collection methods used in this study included (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision. Learning basic Arabic writing skills based on local wisdom introduces students to their culture, creative in writing Arabic, and encourages to better written language.